Odpowiedź:
[tex]7,4-(2,4:\frac{3}{4}+\frac{3}{8}:1,5)=\frac{74}{10}-(\frac{24}{10}:\frac{3}{4}+\frac{3}{8}:\frac{15}{10})=\frac{37}{5}-(\frac{\not12^4}{5}\cdot\frac{4}{\not3_{1}}+\frac{3}{8}:\frac{3}{2})=\\\\=7\frac{2}{5}-(\frac{16}{5}+\frac{\not3^1}{\not8_{4}}\cdot\frac{\not2^1}{\not3_{1}})=7\frac{2}{5}-(\frac{16}{5}+\frac{1}{4})=7\frac{2}{5}-(3\frac{1}{5}+\frac{1}{4})=7\frac{2}{5}-(3\frac{4}{20}+\frac{5}{20})=7\frac{2}{5}-3\frac{9}{20}=[/tex]
[tex]=7\frac{8}{20}-3\frac{9}{20}=6\frac{28}{20}-3\frac{9}{20}=3\frac{19}{20}[/tex]